Human formyl peptide receptor 1 (FPR1) c.32C>T SNP is associated with decreased soluble E-selectin levels. (June 2009) - Benachour, Hamanou; Zaiou, Mohamed; Herbeth, Bernard; Lambert, Daniel; Lamont, John V; Pfister, Michèèle; Siest, Géérard; Tiret, Laurence; Blankenberg, Stefan; Fitzgerald, Peter S; Visvikis-Siest, Sophie
Aims: The human formyl peptide receptor (FPR) is a G protein-coupled chemoattractant receptor that is thought to mediate inflammatory responses. The FPR1 gene is highly polymorphic. In a recent study, the FPR1 c.32C>T SNP, resulting in the amino-acid substitution I11T, was reported to be significantly associated with C-reactive protein levels. Therefore, this study sought to determine if the impact of such a genetic variation extends to other clinical parameters associated with inflammation, including cytokines, adhesion molecules and inflammatory markers.Materials & methods: This study was carried out on a subsample of 325 adults selected from the STANISLAS cohort study. The FPR1 c.32C>T SNP was genotyped using PCR amplification followed by restriction enzyme digestion. Anthropometric measurements and biochemical profiles were assessed for each individual.Results: The allele frequencies of FPR1 c.32C>T were 0.74 for the 32C allele and 0.26 for the 32T allele. Genotype frequencies were 0.55 for C/C, 0.38 for C/T and 0.07 for T/T. After adjusting for age, sex, BMI, alcohol and cigarette consumption, oral contraceptive, antibiotics and anti-inflammatory drug use, statistical analysis (under a recessive model of inheritance) demonstrated that serum E-selectin levels were 68% lower in individuals homozygous for T/T than in those with C/T or C/C genotypes (p = 0.001). However, no significant correlations were found for C-reactive protein or the other 18 tested clinical parameters that were analyzed in this study.Conclusion: The FPR1 c.32C>T SNP may be associated with E-selectin levels in the French population. Although of importance, these findings need confirmation in larger studies.